2020
DOI: 10.1021/acsomega.0c03315
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Phomoxanthone A and B as Protein Tyrosine Phosphatase Inhibitors

Abstract: Phomoxanthone A and B (PXA and PXB) are xanthone dimers and isolated from the endophytic fungus Phomopsis sp. By254. The results demonstrated that PXB and PXA are noncompetitive inhibitors of SHP2 and PTP1B and competitive inhibitors of SHP1. Molecular docking studies showed that PXB and PXA interact with conserved domains of protein tyrosine phosphatases such as the β5-β6 loop, WPD loop, P loop, and Q loop. PXA and PXB could significantly inhibit the cell proliferation in MCF7 cells. Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…To preliminarily understand the potential interactions between 1 and SHP1/SHP2/MEG2, human protein models 4GS0, 3MOW, and 4GE2 were used for molecular docking studies with the stereoisomer of 1 ((1 S ,6’ R ,7’ R )- 1 ). , Their potential interactions are summarized in Table S7. The binding modes were illustrated by PyMOL and Discovery Studio 2.5 software (Figures S34–S36).…”
Section: Resultsmentioning
confidence: 99%
“…To preliminarily understand the potential interactions between 1 and SHP1/SHP2/MEG2, human protein models 4GS0, 3MOW, and 4GE2 were used for molecular docking studies with the stereoisomer of 1 ((1 S ,6’ R ,7’ R )- 1 ). , Their potential interactions are summarized in Table S7. The binding modes were illustrated by PyMOL and Discovery Studio 2.5 software (Figures S34–S36).…”
Section: Resultsmentioning
confidence: 99%
“…Phomoxanthone A (1) is a naturally occurring dimeric tetrahydroxanthone that possesses both an enticing molecular architecture and impressive biological properties (Figure 1). [1][2][3][4][5][6][7][8][9][10] For example, phomoxanthone A is known to have antibacterial, antimalarial, and anticancer activity. It has been observed that 1 is equally as effective at killing both cisplatin sensitive and cisplatin resistant cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…[6] A separate study by Chen and Luo identified phomoxanthone A as a protein tyrosine phosphatase inhibitor. [7] However, the role of these two biomolecular targets in affecting mitochondrial disintegration is unclear leaving open the possibility of phomoxanthone A having more direct target(s) in the mitochondria. This gap in knowledge inspired us to use our synthetic experience to enable the investigation of the biomolecular targets of phomoxanthone A. Herein, we detail the identification of ATP synthase as a biomolecular target of phomoxathone A using a photoaffinity labelling approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phomoxanthone A ( 1 , Scheme ) is a naturally occurring dimeric tetrahydroxanthone with an enticing biological profile, including significant activity toward both cisplatin-sensitive and -resistant cancer cells . The impressive biological properties of phomoxanthone A have spurred investigations into its possible mode of action.…”
mentioning
confidence: 99%